Evidence-based perspective on heart failure and osteoporosis: a systematic review - V. N. Larina; E. S. Shcherbina; V. V. Dryutova; V. G. Larin (Российский кардиологический журнал, 2023)
Aim. To study the prognostic relationship between heart failure (HF) and osteoporosis, as well to search for modern principles and approaches to the management of patients.Material and methods. A search was conducted in the PubMed, RSCI databases from 2012 to 2022 using keywords. The studies were selected according to the PRISMA algorithm.Results. Based on the results, 124 papers were received, and 9 articles were eventually selected. The age of the patients was at least 49 years (mainly elderly patients). The median follow-up ranged from 12 months to 10,5 years. The larger percentage were females.Conclusion. Osteoporosis was associated with the HF risk, and patients with heart failure had a higher risk of accidental fracture due to accelerated bone turnover. The foregoing makes it possible to consider patients with HF as a group of increased risk of osteoporosis and associated fractures, and impaired mineral metabolism as a possible additional cardiovascular risk factor.